2018
DOI: 10.3390/nu10091192
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Inflammatory Bowel Disease: Gains in Adiposity despite High Prevalence of Myopenia and Osteopenia

Abstract: Background: Rising rates of obesity have been reported in patients with inflammatory bowel disease (IBD); however, prospective data is lacking. The aim of this study is to prospectively evaluate body composition in adults with IBD over 24 months. Methods: Whole body dual energy X-ray absorptiometry (DXA) data was performed at 0 months, 12 months, and 24 months. Bone mineral density (BMD), fat mass index (FMI (kg)/height (m2)), appendicular skeletal muscle index (ASMI (kg)/height (m2)), visceral adipose tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 50 publications
3
69
0
1
Order By: Relevance
“…Those mice displayed significant trabecular bone loss with increased TNF-α in bone and colon, which is negatively correlated with OB activity, leading to decreased bone formation rate, but few effects on cortical bone. Interestingly, low dose DSS treatment induces a redistribution of fat storage from subcutaneous to visceral sites, which is reported to be more proinflammatory and consistent with disease pathologies (e.g., Creeping fat accumulation) found in CD patients [146][147][148]. Studies from Harris et al reported a transition in bone composition occurred following active IBD phases [93].…”
Section: Dextran Sulfate Sodium (Dss)supporting
confidence: 55%
“…Those mice displayed significant trabecular bone loss with increased TNF-α in bone and colon, which is negatively correlated with OB activity, leading to decreased bone formation rate, but few effects on cortical bone. Interestingly, low dose DSS treatment induces a redistribution of fat storage from subcutaneous to visceral sites, which is reported to be more proinflammatory and consistent with disease pathologies (e.g., Creeping fat accumulation) found in CD patients [146][147][148]. Studies from Harris et al reported a transition in bone composition occurred following active IBD phases [93].…”
Section: Dextran Sulfate Sodium (Dss)supporting
confidence: 55%
“…In the population with normal BMI, the muscular mass reduction may be still present due to the proportional imbalance of the body components. Bryant et al (31) found that the obesity in obese patients with CD increased with the muscular mass reduction. In clinically treated patients with CD, an elevated BMI does not necessarily mean an improvement of disease condition, and body composition analysis should be done to avoid BMI increase due to water content increase (edema), body fat elevation, and muscular mass reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In many patients with IBD and particularly with CD, the body composition, reflected by as proportions of bone, fat, and lean body mass may be abnormal. Sarcopenia, defined as depletion of muscle mass and impaired muscle function [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82], is an important feature in this disease [70][71][72]81]. Depletion of lean body mass and loss of muscle strength associated with lower QoL and higher mortality and morbidity commonly occurs as part of the aging process [65,77].…”
Section: Skeletal Mass Depletion In Ibdmentioning
confidence: 99%